KETERLEKATAN SOSIAL HOMESTAY DAMANDIRI DUKUH JARAKAN, SAMIRAN, SELO, BOYOLALI - Bagus Ardiyansyah; Briant Nor Pradhuka (Universitas Pendidikan Ganesha, 2025)
This study explores the practice of social embeddedness in the Damandiri homestay program in Dukuh Jarakan, Samiran Village, Selo District, Boyolali. Initiated in 2017, the program has shifted the community’s economy from an agricultural base toward tourism-oriented enterprises. Supported by the Damandiri Foundation and Bank Nusamba, a cooperative was established to manage homestay operations and coordinate revenue-sharing among members. Using a descriptive qualitative approach through observation, interviews, and documentation, the research analyzes the dynamics between homestay owners, cooperative administrators, and local residents. Grounded in Granovetter’s theory of social embeddedness, the findings reveal that homestay economic practices are not solely driven by rational profit calculations but are also shaped by social values, solidarity, reciprocity, and trust. The program has fostered new social relations, created structural dependence on cooperatives, and combined moral economic practices with rational strategies. Overall, the Damandiri homestay illustrates how social capital underpins rural socio-economic transformation and sustains community-based enterprises. Keywords: social embeddedness, homestay, Damandiri Foundation, Samiran Village.